Hairy cell leukemia treatment: where we are now? - Krstevska, Svetlana; Genadieva Stavrikj, Sonja; Sotirova, Tatjana; Spasovski, Dejan; Balkanov, Trajan (ScopeMed, 2011)
Hairy cell leukemia (HCL) is a very rare type of leukemia, in which abnormal B lymphocytes, present in the bone marrow, spleen, and peripheral blood stream, get worse slowly or do not get worse at all. HCL is the disease where patients have pancytopenia with splenomegalia over 90% percent, palpable lymphadenopathy occur in 35% of patients, some form of serious infection eventually developed in over 50% of patients and was the most common cause of death in patients. HCL is dominantly a male disease, with the male-female ratio, ranging from 4:1 to 7:1. Treatment and prognosis of HCL depends on: the number of HC in the peripheral blood or bone marrow, if the spleen is enlarged and on the existence of the visible leukemia infection symptoms. Prognostic factors are similar to the above mentioned and also if the basic disease HCL is aggressive or the number of HC grow slowly and there is no need for treatment. Starting from September 1985 till September 2010, we observed a group with total number of 28 patients (22 males and 6 females) at the age of 30-76 (median range 46 years), all with HCL disease. From the total number of participants, 20 patients (71,43%) received hemotherapy, Cladribine and 8 patients (28,57%) received different type of therapy, such as immunomodulator therapy, surgery or combination of both, without Cladribine. Most effective therapy for HCL, from all of the above mentioned was definitely Cladribine which is dominant with a resulting response rates of 80-100%, where 70-90% of patients were achieving a complete remission, as defined by a complete disappearance of hairy cells in the bone marrow.